Tehnološki napredak i klimatske promjene – Tema u obrazovanju inženjera / Technological Progress and Climate Change – Topic in Engineering Education - Akšamović, Abdulah; Odžak, Senad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
At the beginning of the 21st century, environmental issues became leaders in all areas of human activity without competition. All other essential topics: health, food, energy, water, and air, are predominantly determined by environmental problems. Climate change is a result of excessive CO2 emissions due to the greenhouse effect, air pollution as a result of emissions of harmful substances by thermal power plants, chemical plants, heating boilers, individual furnaces, means of transport; pollution of drinking water, pollution and devastation of arable land, destruction of forests, pollution of rivers due to inadequate wastewater treatment, etc. are problems that require a radical change in man's attitude towards the environment, which leads to the need to reconsider and change the current way of doing business. The paper analyzes the impact of scientific achievements in electrical engineering on the accelerated industrial growth that has led to today's environmental problems. Industrial development is explored in phases (Industry 1.0, Industry 2.0, Industry 3.0, Industry 4.0) regarding the impact of radical changes in doing business. Since we are now in phase 4, the dominant topics are energy transition, energy efficiency, renewable energy sources, recycling, innovation, electric vehicles, networking, Internet of Things (IoT), artificial intelligence, and 5G. Although all the above topics are multidisciplinary, a significant share of electrical engineering is clear. Existing plans and programs in electrical engineering, whether based on the traditional model of education or in the process of innovation, are adapted to new technological trends. As a rule, little or no importance is attached to environmental issues. As one of the answers to the mentioned problem at the Faculty of Electrical Engineering, University of Sarajevo, a new course, “Sustainable Development” was included. The paper briefly describes the content of this course.